Metaphorical Projection in Iraqi Media Discourse and Its Conceptual Connotations - Al-Rubaie , Akram Faraj Abdul-Hussein (Recent Research Advances in Arts and Social Studies Vol. 1, 2023)
The study attempts to demonstrate how metaphors are utilized in Iraqi media discourse and how those concepts are metaphorically projected on Iraqi political and social issues. Metaphor is the motives behind a linguistic expression launched by the producer of the discourse, and an explanation of the hidden purposes of the speech directed to the audience that was made. Many metaphorically projected terminology acquired from foreign media or other sciences were employed by Iraqi editors working in Iraqi media after the American invasion of Iraq in 2003 to depict political problems and the status "these terms need to be investigated to show what their meanings are because. The method used in the present investigation is the survey method. The investigator also uses controlled observation to gather data regarding metaphors borrowed from foreign media and from other sizes. A number of metaphors that are observed used by Iraqi media are either semantically and qualitatively analyzed by the researcher. The metaphors adopted by Iraqi media have been used to refer to various meanings prior to borrowing. The researcher also used a sample of three influential newspapers with contrasting trends: Asabah, Azaman, and Tareeq Ashanti. The study also used three TV channels “Al Iraqis, Al sharqia, and Dijla”. Within two times stages the first stage is after American invasion of Iraq 2003 the other stage is after the parliament elections of 2006 2010 2014 2018 20 21, 21 metaphors are spotted and 14 of them are selected per purposively. This method of data analysis thus represents a continuous, circular process of exploratory analysis that integrates with all phases of the qualitative research. The study reached a number of results, the most prominent of which are: The discourse of the Iraqi print, audio and visual media resorted to portraying the political and social reality in approximate terms whose concepts were borrowed from various sciences and knowledge due to the inability of these media to depict the events that Iraq witnessed after 4/9/2003 using media vocabulary. The dropping of concepts that were borrowed from other knowledge in the Iraqi media discourse in describing the Iraqi reality was partial and was not of long duration, meaning that achieving the goal of representation and analogy of the meaning in the borrowed terms was temporary and faded away after a period of time had passed since its use because it did not express the original meaning. Which it was before the borrowing.